(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The New Education Policy point by point by Overseeing collection of India (NEP 2020) was a tempting change and new news in the midst of the tremendous number of negativities encompassing the world by virtue of the difficulties presented by Covid19 pandemic. The assertion of NEP 2020 was basically surprising by a huge number people. The developments that NEP 2020 has suggested were something that different educationists never saw coming. At any rate the education policy has influenced unendingly school education correspondingly, this article in a general sense spins around NEP 2020 and its effect on significant level preparation. This paper in addition moves toward the earth shattering parts of NEP and assessments what they mean for the continuous education structure.